PENGEMBANGAN MEDIA PEMBELAJARAN SCRATCH-BASED UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMAN 4 SELAYAR - Mudein; Akaram; Rauddin; Mutiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Scratch media can be a computer media that provides activity as a free program. The clever Scratch recreation is bundled in a quiz-like format for college students to explore. It is also a communication device in learning preparation, which aims to encourage learning, draw students' attention, and offer their help to explain problems. The meeting was conducted with one of the teachers, when the perception was taken, the meeting and the perception emerged that the student had challenges in learning the subject, especially the learning fabric. Students are still confused and have difficulty distinguishing cause and effect from what they learn in school. This causes students to not be able to answer questions accurately so that the grades obtained are not good. In the expansion, teachers also face challenges in creating technology-based learning media. In addition, teachers have difficulty finding computer applications that can be used as learning media. The students who take part in these considerations are the students in the lesson who conduct the class based on the results of the interview and perception. This causes students to not be able to answer questions accurately so that the grades obtained are not good. In this consideration, analysts create technology-based media, especially quizzes. This quiz allows students to memorize using visual and kinesthetic learning styles. The test created by the analyst combines different types of images and sounds, students can learn through visual images, students can also learn by playing the test specifically, The learning style that students get by practicing the test specifically may be a kinesthetic mode of learning.